Wurtzite AlPyN1−y: a new III-V compound semiconductor lattice-matched to GaN (0001). (9th October 2020) - Pristovsek, Markus; van Dinh, Duc; Liu, Ting; Ikarashi, Nobuyuki
Abstract: We report on a new member of the III-nitride family, wurtzite AlP y N1− y, tensile strained, or lattice matching (at ≈10.6% P) on (0001) GaN. Unlike lattice-matched AlInN, AlP y N1− y can be grown between 1050 °C to 1250 °C under hydrogen atmosphere in metal-organic vapor phase epitaxy. The transition from GaN to AlP y N1− y is sharp, there is no Ga carry over. Due to the small P content, physical properties like bandgap (around 5.5 eV for lattice match), dielectric function, or polarisation are close to AlN. A first unoptimized AlPN/GaN heterostructure shows a low sheet resistance of 150 ± 50 Ω / □, which makes AlP y N1− y promising for electronic applications.